Harnessing the potential of recently retired physics teachers to mentor new physics teachers. (3rd December 2021) - Cottle, Daniel
Abstract: Three new physics teachers graduating from a university provider of initial teacher education in England were paired with a recently retired physics subject specialist teacher in order to provide informal mentoring during their first year of teaching. The aim of this was to explore if a mentoring intervention of this kind could support teacher knowledge growth of the new physics teachers and influence their retention in the teaching profession. Qualitative data from the study suggests that substantive content of the mentoring discussions that took place addressed issues of general pedagogy and pedagogical content knowledge. The retired teacher mentors were enthusiastic and able to act as mentors. Suggestions emerge for ways of facilitating the mentoring.